Diseño del proceso de producción de harina de mosca soldado negra (Hermetia Illucens) alimentadas con pulpa de café. (2022)
This research work takes into account the concern for the increase of waste in the coffee industry focused directly on coffee pulp, and therefore seeks to implement sustainable and environmentally friendly alternatives such as silage and the use of microorganisms that help with the decomposition of such organic matter in an efficient and prompt manner, such as the black soldier fly (Hermetia Illucens). This work will focus mainly on the use of the black soldier fly (Hermetia Illucens) for the treatment and degradation of organic residues from the coffee industry, for which a process design is proposed for the production of black soldier fly (Hermetia Illucens) meal fed with coffee pulp. The characterization of the coffee pulp will allow us to identify the composition of the pulp and with this to see the feasibility of the use of the black soldier fly (Hermetia Illucens) in it, to establish operating conditions for the development of the fly and with this to obtain a higher percentage of transformation of the coffee pulp and finally the design of the production process of black soldier fly (Hermetia Illucens) flour.